1993
DOI: 10.1063/1.352643
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of Pd/Co multilayer films studied by Hall effect

Abstract: The magnetic properties and Hall effects of Pd/Co multilayer films fabricated by thermal evaporation have been studied using the Hall hysteresis loop measurement. The polarity of the Hall hysteresis loops of Pd/Co multilayer changed between 4 and 5 monolayers (ML) of Pd. It was speculated that the reason for this phenomena is the change of the position of Fermi level of 3d band in Pd/1Co multilayer from lower half of the band to upper half of the band depending on the Pd thickness. The Hall resistivities as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Since Co/Pd is one of the promising candidates for perpendicular magnetic recording technology, [3][4][5] there are several AHE studies on thin Co-Pd alloys and {Co/Pd} n multilayers. In chronological order, Kim et al 10 explored the Pd thickness dependence of the AHE of {Co/Pd} multilayers prepared by thermal evaporation at room temperature and observed a polarity change of the AHE between 4 and 5 monolayers of Pd for a fixed Co thickness of one monolayer. It was speculated that this can be attributed to a change of the position of the Fermi level with increasing Pd thickness.…”
mentioning
confidence: 99%
“…Since Co/Pd is one of the promising candidates for perpendicular magnetic recording technology, [3][4][5] there are several AHE studies on thin Co-Pd alloys and {Co/Pd} n multilayers. In chronological order, Kim et al 10 explored the Pd thickness dependence of the AHE of {Co/Pd} multilayers prepared by thermal evaporation at room temperature and observed a polarity change of the AHE between 4 and 5 monolayers of Pd for a fixed Co thickness of one monolayer. It was speculated that this can be attributed to a change of the position of the Fermi level with increasing Pd thickness.…”
mentioning
confidence: 99%
“…There are several reports on the reversal of the EHE polarity, particularly in Co-based materials. The phenomenon was observed in CoPd alloys [12] and multilayers [13,14] when concentration or a relative thickness ratio between the components was changed, and when a layer of FeMn antiferromagnet was added [15]. It was suggested [13] that the change of the position of Fermi level and, therefore shift of the majority carriers from electrons to holes, is the reason for the change of EHE polarity.…”
mentioning
confidence: 99%
“…From studies of RE-TM amorphous alloy films it is known that the sign of the Hall resistivity changes at the compensation composition due to the change in spin direction [25][26][27][28], meaning that either the Fe or Tb magnetic moment dominates in the perpendicular anisotropy. For Tb/Fe multilayers with different layer thickness it was also shown that the Hall voltage dependence is determined by the interface [29,30]. For Fe/Au/Tb trilayers the indirect exchange between Fe and Tb goes by means of polarized conduction electrons of Au.…”
Section: The Sign Change Of the Couplingmentioning
confidence: 99%